Analisis Angkutan Sedimen Melayang Di Bagian Hilir Saluran Drainase Sungai Raya Dalam, Peri-Urban Kota Pontianak, Kalimantan Barat - Hanun, Sartika Ananta; Nurhayati, Nurhayati; Umar, Umar (Universitas Tanjungpura, 2025)
Suspended sediment transport is an important phenomenon in the dynamics of drainage channel estuaries that can affect the morphological stability and quality of the aquatic environment. This study aims to analyze the pattern of sediment transport floating at the mouth of the drainage channel of Sungai Raya Dalam, peri-urban area, West Kalimantan Province. The methods used include water sampling, hydrodynamic measurements, and laboratory analysis to determine the concentration of suspended sediments. The results show that tidal variations and flow discharge have a significant effect on the distribution of floating sediment. During high tide, there is an increase in sediment concentration due to greater current turbulence, while at low tide, there is significant deposition. This study provides insights into more effective sedimentation management and drainage planning in estuarine areas. Based on the results of the study, the amount of sediment transportation floating in the drainage channel of Sungai Raya Dalam ranges from 0.008 kg/s to 0.143 kg/s.